Stock Flow Diagram Analysis on Solid Waste Management in Malaysia - Faridah, Zulkipli; Zulkifli, Mohd Nopiah; Noor Ezlin, Ahmad Basri; Cheng, Jack Kie (AIP Publishing LLC, 2016)
The effectiveness on solid waste management is a major importance to societies. Numerous generation of solid waste from our daily activities has risked for our communities. These due to rapid population grow and advance in economic development. Moreover, the complexity of solid waste management is inherently involved large scale, diverse and element of uncertainties that must assist stakeholders with deviating objectives. In this paper, we proposed a system dynamics simulation by developing a stock flow diagram to illustrate the solid waste generation process and waste recycle process. The analysis highlights the impact on increasing the number of population toward the amount of solid waste generated and the amount of recycled waste. The results show an increment in the number of population as well as the amount of recycled waste will decrease the amount of waste generated. It is positively represent the achievement of government aim to minimize the amount of waste to be disposed by year 2020.